Chemical analysis and molecular models for calcium-oxygen-carbon interactions in black carbon found in fertile amazonian anthrosoils - Archanjo, Bráulio Soares; Araújo, Joyce R.; Silva, Alexander M.; Capaz, Rodrigo B.; Falcão, Newton P.S.; Jório, Ado; Achete, Carlos Alberto (Environmental Science and Technology, 2014)
Carbon particles containing mineral matter promote soil fertility, helping it to overcome the rather unfavorable climate conditions of the humid tropics. Intriguing examples are the Amazonian Dark Earths, anthropogenic soils also known as "Terra Preta de Índio (TPI), in which chemical recalcitrance and stable carbon with millenary mean residence times have been observed. Recently, the presence of calcium and oxygen within TPI-carbon nanoparticles at the nano- and mesoscale ranges has been demonstrated. In this work, we combine density functional theory calculations, scanning transmission electron microscopy, energy dispersive X-ray spectroscopy, Fourier transformed infrared spectroscopy, and high resolution X-ray photoelectron spectroscopy of TPI-carbons to elucidate the chemical arrangements of calcium-oxygen-carbon groups at the molecular level in TPI. The molecular models are based on graphene oxide nanostructures in which calcium cations are strongly adsorbed at the oxide sites. The application of material science techniques to the field of soil science facilitates a new level of understanding, providing insights into the structure and functionality of recalcitrant carbon in soil and its implications for food production and climate change. © 2014 American Chemical Society.
Keywords: Calcium; Climate Change; Infrared Spectroscopy; Iodine; Molecular Modeling; Molecular Oxygen; Soils; Transmission Electron Microscopy; X Ray Photoelectron Spectroscopy; X Ray Spectroscopy; Amazonian Dark Earths; Anthropogenic Soils; Climate Condition; Energy Dispersive X Ray Spectroscopy; Fourier Transformed Infrared Spectroscopy; Material Science; Mean Residence Time; Scanning Transmission Electron Microscopy; Carbon; Black Carbon; Calcium; Calcium Oxide; Carbon; Oxygen; Soil Organic Matter; Anthropogenic Source; Black Carbon; Calcium; Carbon; Chemical Analysis; Climate Change; Food Production; Humid Tropics; Molecular Analysis; Oxygen; Soil Fertility; Soil Pollution; Adsorption; Cation Exchange; Chemical Bond; Climate Change; Density Functional Theory; desorption; Food Industry; Humic Substance; Infrared Spectroscopy; Molecular Interaction; Ph; Scanning Transmission Electron Microscopy; Soil Chemistry; Soil Fertility; X Ray Photoelectron Spectroscopy; Amazonia; Calcium; Carbon; Models, Molecular; Molecular Conformation; Nanostructures; Oxygen; Photoelectron Spectroscopy; Soil; Soot; Spectrometry, X-ray Emission